In vitro shoot multiplication of Morus nigra by combinations of plant growth regulators. Issue 1 (November 2021) - Larekeng, S H; Arsyad, M A; Annisa, A M; Restu, M
Abstract: Mulberry (Morus nigra L) is a dicotyledonous plant in the family Moraceae which often used for silkworms' breeding. Mulberry propagation still uses conventional technology, such as cuttings and graftings. The problem of mulberry propagation is the low productivity of mulberry gardens. However, tissue culture is a technique of isolating plant parts in the form of organs, cell tissues, and protoplasms that is effective and efficient in order to get uniform and superior plants in a short amount of time. For mulberry growth, the right combination of the Plant Growth Regulator (PGR) in the form of Kinetin, IAA, IBA is needed. Data were analyzed using R-statistic software. The results showed that M6 media (MS + Kinetin 1.5 + 1 IAA) was the best combination of media for the number of shoots, leaf length, and number of roots, with 80% of live explant percentage. Propagation via tissue culture such as clonal propagation, organogenesis, and somatic embryogenesis in callus cultures followed by generation of shoots/plantlets represents a potential effective propagation method in the future.